2011
DOI: 10.1089/ten.tec.2010.0172
|View full text |Cite
|
Sign up to set email alerts
|

Tubular Perfusion System for the Long-Term Dynamic Culture of Human Mesenchymal Stem Cells

Abstract: In vitro culture techniques must be improved to increase the feasibility of cell-based tissue engineering strategies. To enhance nutrient transport we have developed a novel bioreactor, the tubular perfusion system (TPS), to culture human mesenchymal stem cells (hMSCs) in three-dimensional scaffolds. This system utilizes an elegant design to create a more effective environment for cell culture. In our design, hMSCs in the TPS bioreactor are encapsulated in alginate beads that are tightly packed in a tubular gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(112 citation statements)
references
References 64 publications
7
105
0
Order By: Relevance
“…However, after this time, the number of cells decreased, and after 21 days, half of the cells had died, probably because of the culture conditions used (Figure 4b). Indeed, some authors have shown that to maintain viable cells inside 3-D scaffolds for long periods, it is necessary to force medium perfusion inside the scaffold using dynamic culture conditions [27][28][29] .…”
Section: Resultsmentioning
confidence: 99%
“…However, after this time, the number of cells decreased, and after 21 days, half of the cells had died, probably because of the culture conditions used (Figure 4b). Indeed, some authors have shown that to maintain viable cells inside 3-D scaffolds for long periods, it is necessary to force medium perfusion inside the scaffold using dynamic culture conditions [27][28][29] .…”
Section: Resultsmentioning
confidence: 99%
“…31 Briefly, an L/S multichannel pump system (Cole Palmer) was used to drive flow (2 mL/min) through a tubing circuit. The flow rate was chosen based on previous data regarding EPC differentiation into EC-like cells.…”
Section: Bioreactor Designmentioning
confidence: 99%
“…We have previously demonstrated the successful application of the TPS bioreactor in the development and support of various tissue engineering constructs. 23,[29][30][31] In contrast to work showing the differentiation of EPCs in arterial shear stress environments, we chose to demonstrate cell seeding and differentiation in venous shear stress conditions given the lack of available TEVGs for venous conditions and their application in conditions such as congenital heart disease. Thus, it may be advantageous to understand the fate of EPCs within the venous system.…”
Section: Introductionmentioning
confidence: 99%
“…The tubular perfusion bioreactors (TPBs) [49], are easily fabricated allowing cell construct encapsulatation in tightly packed spherical beads [50]. One study found hBMSCs encapsulated in alginate beads had 1.6 times more cells [49].…”
Section: Tubular Perfusion Bioreactormentioning
confidence: 99%
“…One study found hBMSCs encapsulated in alginate beads had 1.6 times more cells [49]. Others found hBMSCs secrete more GAGs in the dynamic environment of a TPB as evidenced by Alcian blue staining [51].…”
Section: Tubular Perfusion Bioreactormentioning
confidence: 99%